Pelatihan Public Speaking Untuk Alumni Jurusan Manajemen Fakultas Bisnis Unika Widya Mandala Surabaya - Fenika Wulani; Veronika Rahmawati; C. Marliana Junaedi; Monica Adjeng Erwita (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service aims to provide additional knowledge-based and practical insights in becoming a business professional in terms of Public Speaking, special topics of Personal Branding and Grooming. Participants are alumni of the Management Department of the Faculty of Business, Widya Mandala, Surabaya. There were 10 participants who registered for the Community Service. However, 9 people attended the meeting. The results of the evaluation of this activity showed an average value of 4.44 which indicated that the participants rated it very well in providing training, providing material, and other facilities. The participants seemed enthusiastic, it was seen from their comments, input, and the desire for training with advanced and other topics.